Teachers evaluation on the implementation of j-QAF Quranic recitation models - Ab. Halim Tamuri; Ahmad Munawar Ismail; Amal Hayati Md. Noor; Mohd Izzuddin Mohd Pisol (Universiti Kebangsaan Malaysia, 2013)
This survey aimed to identify the level of implementation in the j-QAF Quranic Recitation program (6 Months Model of Khatam al-Quran, Tasmik Model, Asuhan Tilawah al-Quran and al-Quran Literacy Camp). This study used a quantitative approach (questionnaire) to gather information from 240 Islamic Education and j-QAF teachers from 24 primary schools in Kuala Selangor, Klang and Hulu Langat district in Selangor. Data were analyzed descriptively using frequency, percentage and mean. Pearson’s test was also conducted to examine the relationships between the implementation of these models. Generally, from the data analysis, it was found that the level of implementation in the models of Quranic Recitation j-QAF were high. The study found that there were siginificant relationships between the teachers’ evaluation on the four models of Quranic Recitation j-QAF.